Economic sustainability assessment of Mediterranean crops: A comparative Life Cycle Costing (LCC) analysis - Spada, Emanuele; Stillitano, Teodora; Falcone, Giacomo; Iofrida, Nathalie; Gulisano, Giovanni; De Luca, Anna Irene (Frontiers in Sustainable Food Systems, 2022)
The production of food with beneficial health effects is at the attention of consumer entrepreneurs and public decision-makers. Plants with established health benefits such as almonds, olives from which olive oil is made, and figs have always been cultivated in the Mediterranean basin. In the past, these three crops were widely cultivated in Italy, particularly in the southern part, where the best soil and climate conditions persisted. Today, however, almond and fig production is at an all-time low. The present work aims to assess the economic sustainability of investments in shell almond, olive and fig farms by integrating Life Cycle Costing (LCC) methodology with specific economic indicators. In addition, a comparison between the three crops is made based on all economic results. The analysis allowed for the consideration of all costs over the entire life cycle of the investments, streamlining business decision-making for the choice between different alternatives. The results demonstrated greater economic profitability of investments in shelled almonds and dried figs and an adequate level of profitability. Lower, on the other hand, were the results for olive trees. In this context, the production of almonds and figs could represent an important agribusiness chain, useful for the improvement of the rural economy.